Overexpression of Isl1 under the Pax2 Promoter, Leads to Impaired Sound Processing and Increased Inhibition in the Inferior Colliculus - Chumak, Tetyana; Tothova, Diana; Filova, Iva; Bures, Zbynek; Popelar, Jiri; Pavlinkova, Gabriela; Syka, Josef (International journal of molecular sciences, 2021)
The LIM homeodomain transcription factor ISL1 is essential for the different aspects of neuronal development and maintenance. In order to study the role of ISL1 in the auditory system, we generated a transgenic mouse (Tg) expressing Isl1 under the Pax2 promoter control. We previously reported a progressive age-related decline in hearing and abnormalities in the inner ear, medial olivocochlear system, and auditory midbrain of these Tg mice. In this study, we investigated how Isl1 overexpression affects sound processing by the neurons of the inferior colliculus (IC). We recorded extracellular neuronal activity and analyzed the responses of IC neurons to broadband noise, clicks, pure tones, two-tone stimulation and frequency-modulated sounds. We found that Tg animals showed a higher inhibition as displayed by two-tone stimulation; they exhibited a wider dynamic range, lower spontaneous firing rate, longer first spike latency and, in the processing of frequency modulated sounds, showed a prevalence of high-frequency inhibition. Functional changes were accompanied by a decreased number of calretinin and parvalbumin positive neurons, and an increased expression of vesicular GABA/glycine transporter and calbindin in the IC of Tg mice, compared to wild type animals. The results further characterize abnormal sound processing in the IC of Tg mice and demonstrate that major changes occur on the side of inhibition.
Keywords: mozek; exprese genu; Humans; Promoter Regions, Genetic; Auditory Threshold; Gene Expression; Mice, Transgenic; Evoked Potentials, Auditory, Brain Stem; Transcription Factors; Inferior Colliculi; sluch; inhibition; Female; auditory system; myši transgenní; Auditory Perception; Hearing; LIM-Homeodomain Proteins; lidé; transcription factor ISL1; zvířata; neurony; myši; sluchové kmenové evokované potenciály; sound processing; Mice; sluchový práh; ženské pohlaví; Male; Brain; proteiny s homeodoménou LIM; Neurons; transkripční faktory; Animals; inferior colliculus; PAX2 Transcription Factor; mužské pohlaví; promotorové oblasti (genetika); sluchová percepce; colliculus inferior; transkripční faktor PAX2